WEB-BASE 3D SOFTWARE UNTUK PERENCANAAN DAN PELAKSANAAN TRAJECTORY PEMBORAN BERARAH - Allen Haryanto Lukmana; Aris Buntoro; Avista Oktaviana Putri Utami (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
In drilling activities there are several types of trajectories, one of which is directional drilling. In a directed drilling operation, the engineer must carry out a design of the well trajectory and then do a calculation then the results are used as a reference for the calculation of the well trajectory after the drilling operation. In this study a system was built in the application to help engineers perform calculations on Plan Trajectory data and Survey Trajectory data so that further evaluation can be made of deviations that occur by implementing the Minimum Of Curvature calculation method.While the system development method used is the Waterfall method which will be divided into three stages in building a system, namely problem analysis, gathering system requirements and system design. The method of data collection is done by collecting secondary data sources. The application is built with the support of PHP, Javascript and PHPMyAdmin programming languages for database management.From the results of the analysis, design and testing carried out successfully built 3D Application Planning and Implementation of Drilling Trajectory Leading to the